Strategies for rendering multilingualism in subtitling for the deaf and hard of hearing - Szarkowska, Agnieszka; Żbikowska, Jagoda; Krejtz, Izabela (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
In this paper we present a set of strategies for rendering the presence of multiple languages in multilingual films in subtitling for the deaf and hard of hearing (SDH): vehicular matching, explicit attribution, colour-coding and linguistic homogenisation. We also report on an online study among deaf and hard of hearing Polish participants regarding their preferences for specific SDH strategies. The findings show that, even when they do not know the foreign language involved, most participants prefer more informative strategies where indications of multilingualism are made explicit.